Differences between ACC/AHA and ESC Guidelines on antiplatelet therapy in patients with acute coronary syndromes - Huber, Kurt; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2013)
Note: The review process for this Editorial was fully handled by Christian Weber, Editor in Chief.